2016
DOI: 10.1503/cmaj.151171
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of palliative care among patients with advanced cancer and their caregivers

Abstract: Interpretation: There is a strong stigma attached to palliative care, which may persist even after positive experiences with an early palliative care intervention. Education of the public, patients and health care providers is paramount if early integration of palliative care is to be successful. AbstractCMAJ Podcasts: author interview at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
255
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 300 publications
(286 citation statements)
references
References 33 publications
17
255
2
12
Order By: Relevance
“…Moreover, the ongoing definition of palliative care for patients and their caregivers is care provided at the end of life, although a worldwide change in this definition was made over a decade ago. 22 A name change can be taken into consideration, although it is essential that such change involves the way palliative care is Oncological homecare Oliveira MBP, Souza NR, Bushatsky M, Dâmaso BFR, Bezerra DM, Brito JA portrayed. Thus, it is clear that wide basic education is required to guarantee a greater understanding of what palliative care represents and involves.…”
Section: Family Members/caregivers' Understanding Of Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ongoing definition of palliative care for patients and their caregivers is care provided at the end of life, although a worldwide change in this definition was made over a decade ago. 22 A name change can be taken into consideration, although it is essential that such change involves the way palliative care is Oncological homecare Oliveira MBP, Souza NR, Bushatsky M, Dâmaso BFR, Bezerra DM, Brito JA portrayed. Thus, it is clear that wide basic education is required to guarantee a greater understanding of what palliative care represents and involves.…”
Section: Family Members/caregivers' Understanding Of Palliative Carementioning
confidence: 99%
“…Thus, it is clear that wide basic education is required to guarantee a greater understanding of what palliative care represents and involves. 22 …”
Section: Family Members/caregivers' Understanding Of Palliative Carementioning
confidence: 99%
“…In a recent survey, palliative care clinics were available at 59% of National Cancer Institute (NCI) centersand22%ofnon-NCIcenters [38].Evenatcenterswithaccess tosuchclinics,referralstendtooccurlateinthediseaseprocess [40], althoughoncologistswith palliativecaretrainingtendtoreferearlier in the course of illness [3]. One reason for late referrals is the faulty perception by those providing and receiving cancer care that palliative care is synonymous with "end-of-life" care [41][42][43][44]. This has led some services to change their name to "supportive care" [41] and has galvanized a broader interest in the education of both providers and the public about palliative care [45].…”
Section: P-347cmentioning
confidence: 99%
“…Although that task is clearly part of the role of palliative care providers, it is but a subset of the scope of palliative medicine practice. In a recent study, Zimmermann et al 11 showed that cancer patients and caregivers associate the term "palliative care" with death and end of life, and they are therefore reluctant to be referred early. That stigmatization must be overcome if early integration of palliative care is to be successful.…”
Section: What Are the Barriers To Implementation?mentioning
confidence: 99%